The fire never goes out : a memoir in pictures - Stevenson, Noelle (HarperTeen, 2020)
"In a collection of personal comics that span eight years of her young adult life, author-illustrator Noelle Stevenson charts the highs and lows of being a creative human in the world."--Provided by publisher.